Enhancing synchronous hybrid learning with telepresence robots: a PEPCII pedagogical design model for remote and onsite student engagement - Kasuk, Tiina; Leoste, Janika; Virkus, Sirje (Frontiers in Education, 2025)
IntroductionThe aim of this article is to provide a report on the development of a pedagogical design model for the effective adoption of telepresence robots (TPRs) in synchronous hybrid learning settings.MethodsFollowing the design thinking approach, we conducted three qualitative studies. In the first study, we examined the needs of and opportunities for using TPRs in education as well as some of the related challenges. This was based on the personal experiences of six academic staff members in two Estonian higher education institutions. Building on the first study, we designed a 13-week synchronous hybrid undergraduate-level course using TPRs. The course was delivered to six students. Based on the students’ homework and written feedback, the first prototype of a pedagogical design model was subsequently developed. In the third study, this model was piloted with 56 teachers by means of a two-hour hands-on synchronous hybrid workshop.ResultsBased on the teachers’ feedback, the prototype was further improved and the PEPCII Pedagogical Design Model was completed. The PEPCII model comprises six central components that address key barriers to the adoption of TPR-s in education: Physical Operational and Educational Environment, Ethical and Cybersecurity Considerations, Cognitive and Physical Limitations, Pedagogical Integration, Inclusive Access and Engagement, and Instructional Methods.DiscussionThe PEPCII model addresses critical barriers to TPR adoption in education. Future research is required to validate the model in varied classroom settings over longer durations, and to assess impacts on engagement and well-being of TPR users, on-site students, and instructors.